Factions in Nondemocracies: Theory and Evidence From the Chinese Communist Party - Francois, Patrick; Trebbi, Francesco; Xiao, Kairong (Econometrica, 2023)
This paper theoretically and empirically investigates factional arrangements within the Chinese Communist Party (CCP), the governing political party of the People's Republic of China. Using detailed biographical information of political elites in the Central Committee and provincial governments, we present a set of new empirical regularities within the CCP, including systematic patterns of cross‐factional balancing at different levels of the political hierarchy and substantial faction premia in promotions. We propose and estimate an organizational economic model to characterize factional politics within single‐party nondemocratic regimes and its economic implications.